2018
DOI: 10.1111/1462-2920.14447
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen chlorosis in unicellular cyanobacteria – a developmental program for surviving nitrogen deprivation

Abstract: Summary Cyanobacteria evolved sophisticated mechanisms allowing them to cope with environmental depletion of combined nitrogen. Here, we describe progress in understanding the processes involved in acclimation of nondiazotrophic cyanobacteria to nitrogen shortage, known as nitrogen chlorosis. The process includes immediate metabolic changes and degradation of light harvesting complexes as well as long‐term acclimation responses. Consequently, quiescent cells substantially differing from vegetative cells are ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 95 publications
3
47
0
Order By: Relevance
“…Consistent with our data, Ogawa and Sonoike (2016) determined the "true" maximum quantum yield of PSII (Fv/Fm) in Synechocystis by eliminating the interference from phycocyanin fluorescence and revealed that the Fv/Fm around 0.8, which was similar to the value observed in land plants, substantially decreased with N starvation. Inactivation of PSII may reduce a risk of photodamage from light energy that exceeds the photosynthetic capacity in N-starved cells with decreased cellular metabolism (Forchhammer and Schwarz, 2019).…”
Section: Disorganization Of the Thylakoid Membrane Components By N Stmentioning
confidence: 99%
See 3 more Smart Citations
“…Consistent with our data, Ogawa and Sonoike (2016) determined the "true" maximum quantum yield of PSII (Fv/Fm) in Synechocystis by eliminating the interference from phycocyanin fluorescence and revealed that the Fv/Fm around 0.8, which was similar to the value observed in land plants, substantially decreased with N starvation. Inactivation of PSII may reduce a risk of photodamage from light energy that exceeds the photosynthetic capacity in N-starved cells with decreased cellular metabolism (Forchhammer and Schwarz, 2019).…”
Section: Disorganization Of the Thylakoid Membrane Components By N Stmentioning
confidence: 99%
“…Doello et al (2018) revealed that the N-starved chlorotic cells maintain ATP levels to 20-25% of nutrientsufficient cells. As discussed by Forchhammer and Schwarz (2019), the cyclic electron transport around PSI may be retained in N-starved cells to maintain ATP levels and cell viability during chlorosis.…”
Section: Disorganization Of the Thylakoid Membrane Components By N Stmentioning
confidence: 99%
See 2 more Smart Citations
“…First, dismantling of the PBS releases nutrients in the form of amino acids; second, reduced cellular metabolism under starvation might lead to over-excitation and therefore, degradation and uncoupling of the PBS serve as a mechanism to reduce electron transfer rate under such conditions. Multiple studies of PBS degradation have provided insight into the mechanism underlying this process (Forchhammer and Schwarz 2018).…”
Section: Introductionmentioning
confidence: 99%